Development of Theory and Practice in Fermentation and Secondary Fermentation of Beer. - G. BASAŘOVÁ (Kvasný průmysl, 2002)
The theory of the beer fermentation process experienced  a long development, in the 19th century, from the mechanical  interpretation through the explanation on the basis of simply  chemical reactions down to the understanding of the  biological anaerobic process of fermentation with  participation of brewery yeast and to the importance of  enzyme reactions. Then, the measures were followed by  isolation and introduction of pure yeast cultures in the  production process in breweries and by findings regarding  infectious microorganisms in the brewing process.  In the nineteen fifties, the cognition of the yeast  metabolism and of its mechanisms provided for fast  development of modern laboratory techniques, mainly of the  chromatographic and electrophoretic ones.  In the nineteen eighties, the research of transport of  saccharides into cell and of their gradual attenuation gave  precision to the demands on composition of hopped wort and  enabled to optimize the fermenting process, above all in  insertion of CKT. Equally, the research clarified the  inhibitive action of the glucose level in the medium for  attenuation of maltose. The knowledge of the gradual  absorption of aminoacids in hopped wort by brewery yeasts  helped e.g. to explain the increased formation of vicinale  diketones during the long-term soaking of CKT and to optimize  this production sector.  In the same period of nineteen eighties, the gene engineering  started to win through in the brewing industry as well  bringing results not only in new barley varieties but even in  yeast strains with new introduced properties.  The development in discovery of importance of the  physicochemical and biochemical properties of hopped wort and  of the genetically coded metabolic abilities of yeast has  broadened gradually the number of followed-up criteria. The  sciences were intensified as regards the genetically coded  properties of the individual yeast strains and of their  influence on the technology course and on the quality of  beer. The research results specified the criteria of hopped  wort, yeast and technologic processes, particularly since the  nineteen sixties, in connection with development in  realization in practice of the high-volume vessels for  fermentation and secondary fermentation and, in the nineteen  seventies, due to the increasing claims for sensory stability  of beer. The gradual cognition of the reactions in formation  of components of the old taste of beer affected the change of  some previously required values of malt and hopped wort.The theory of the beer fermentation process experienced  a long development, in the 19th century, from the mechanical  interpretation through the explanation on the basis of simply  chemical reactions down to the understanding of the  biological anaerobic process of fermentation with  participation of brewery yeast and to the importance of  enzyme reactions. Then, the measures were followed by  isolation and introduction of pure yeast cultures in the  production process in breweries and by findings regarding